2019
DOI: 10.1021/acs.iecr.9b03491
|View full text |Cite
|
Sign up to set email alerts
|

Bromination Modification of Butyl Rubber and Its Structure, Properties, and Application

Abstract: The properties of bromobutyl rubber (BIIR) are closely related to its bromine content and the bonding structure of the bromine atom with the BIIR molecular chain. We here investigated the effect of these two factors on BIIR properties. We prepared BIIR with a predominant exomethylene allyl (EXO) or endo-bromomethyl olefin (ENDO) microstructure at different levels of bromine content by controlling the conditions of bromination. BIIRs with a high bromine content had low permeability coefficients: the permeabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…[17] MgO may be added to help control cure rate and scorch. [18] Alkaline ingredients do not improve the safety of scorch in bromobutyl rubber-sulfur cure without ZnO. The proposed mechanism of crosslinking of BIIR with ZnO and MgO is depicted in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…[17] MgO may be added to help control cure rate and scorch. [18] Alkaline ingredients do not improve the safety of scorch in bromobutyl rubber-sulfur cure without ZnO. The proposed mechanism of crosslinking of BIIR with ZnO and MgO is depicted in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…52 The dispersed calcium stearate scavenges the eliminated HBr and suppresses the conversion from exo-to endomicrostructure. Cao et al 53 reported the preparation of BIIR with a predominantly exo-and endo-microstructure and different levels of bromine content by controlling the conditions of bromination. BIIRs with predominantly endo-microstructure and high bromine content show a high cure rate and excellent compatibility with natural rubber (NR), which markedly improved the mechanical performance of the NR/BIIR blend vulcanizate.…”
Section: Halogenationmentioning
confidence: 99%
“…Schematic representation of the mechanism of IIR bromination process (panels a–d showing different steps for the formation of endo bromobutyl and the addition product). …”
Section: Postpolymerization Modification Of Butyl Rubbermentioning
confidence: 99%
“…Curing or crosslinking sites in polymer chains are incorporated by addition of IP units. Further halogenation of butyl rubber leads to the formation of high curing halobutyl (chlorobutyl and bromobutyl) rubbers 13 …”
Section: Introductionmentioning
confidence: 99%